IMPLEMENTASI PROGRAM KELUARGA HARAPAN DI DINAS SOSIAL KABUPATEN POSO - Tirani, Oktavia (Katalogis, 2017)
This study aimed to analyze the implementation of expected family program Program at Social Affair Department in Poso Regency. Family hope program was Government’s policy through the Ministry of Social Affairs to help people who were categorized as self-help groups (keluarga swadaya masyarakat – KSM) to fulfil their health and education needs, and in order that the PKH participants be able to carry out their obligations in accordance with the provisions. In general, the task of implementation theory is to link the public policy goals with the results of Government’s activities. The models which can be used to analyze a policy implementation is the theory of George Edward III to explain the process of policy implementation, namely: 1) Communications, 2) Resources, 3) Dispositions (Implementers’ Attitudes), 4) Bureaucratic Structure.